The impact of work-life integration to the productivity of the employees of eperformax T-mobile account - Arnold Espiritu, Kyle Samantha Mogado, Danica Rose Repulledo, Roxanne Cielo Rodriguez, Yanna Bethany Torres 4 0 16; 5
Introduction Advocating change in the way work is done and life is lived meets resistance because it places these cherished identities at risk. As the world constantly changes, especially that the world is still recovering from the pandemic, work-life integration was recognized during the crisis of COVID 19 pandemic as it is seen as an advantage in the organization. The increasing adoption of employer sponsored work-life integration is partly due to the increasing societal pressure for employers to respond to workers' personal needs. It is also driven by employers' mandate to build a highly committed and engaged workforce. Work life integration refers to the approach of effective and efficient synchronization among time, energies & efforts in a way that enables workers to fulfill their work, family, and societal obligations. For the effectiveness of work life integration, organizations are trying to implement policies that care for the employee's personal issues and also ensure organizational productivity. The workplace, therefore, represents an important target towards which solution should be directed to manage productivity and performance of an employee. Overall, the main objective of human resource practices in an organization is to improve employee productivity and performance to sustain the organization's competitive advantage.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2